The relationship between the TSH values and the Tpeak - Tend interval duration in hypothyroid patients receiving Levothyroxine treatment - Findikli Hüseyin Avni; Tutak Ayşe Şahin; Aydin Hakan (Sciendo, 2019)
Introduction. Changes in thyroid hormone level can affect the cardiovascular system. The aim of this study was to show how the Tpeak -Tend (Tpe) interval, which is a new marker of ventricular arrythmia, is affected in patients who have become euthyroid following Levothyroxine treatment for hypothyroidism, as this has not been examined previously in literature.